(untitled) (Symposium on Natural and Applied Sciences, 2026)
Gallbladder empyema, the suppurative form of acute cholecystitis, accounts for a disproportionate share of cholecystitis-related deaths and prolonged hospital admissions [1]. Its pathogenesis converges two overlapping biological failures: inadequate containment of gram-negative bacteria, and impaired cellular resistance to reactive oxygen species generated during ischaemic injury of the gallbladder wall. Toll-like receptor 4 (TLR4) governs bacterial containment through pattern recognition of lipopolysaccharide [2], while mitochondrial superoxide dismutase 2 (SOD2) scavenges superoxide anions at the inner mitochondrial membrane under inflammatory hypoxia [3]. The Asp299Gly missense variant of TLR4 (rs4986790) attenuates NF-kappaB signalling, and the Ala16Val substitution of SOD2 (rs4880) reduces mitochondrial enzyme import by altering the targeting sequence. Each polymorphism individually associates with increased susceptibility to severe inflammatory disease, but their joint clinical effect in the specific setting of biliary empyema has not been investigated in any published cohort to date.